(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2025)
This article presents the findings of a generic qualitative research study that investigated 20 pre-service teachers’ experiences and perspectives of a group worksheet discussion in a third-year English literary studies module that is part of a Bachelor of Education degree in Intermediate Phase teaching. The participants were interviewed, both individually and in focus groups, and their assessment tasks were analysed. The task was based on the novel, The Book Thief, by Markus Zusak. The academic essay is the dominant form of both formative and summative assessments in many academic disciplines, but especially in literary studies. This is problematic in some ways as most students who enter university do not speak English as their first language and generally struggle with expressing their ideas in academic writing. Additionally, many students do not have sufficient knowledge of history, and group work can supplement historical knowledge gaps that students may have. I argue that group work is underused in English literary studies modules. The findings of this research indicated that group work discussions can facilitate collaborative, inquirybased and problem-based learning to advance knowledge of history that facilitates skills development in literary studies. These skills include close reading, textual analysis and disciplinary content knowledge.